A nickel-iron-manganese-copper quaternary positive electrode material and its precursor, preparation method and application

By developing a method for preparing nickel-iron-manganese-copper quaternary cathode material precursors, the problem of structural instability in layered transition metal oxide sodium-ion batteries was solved, achieving a gradient distribution of copper elements and improved electrochemical performance, making it suitable for the industrial production of sodium-ion battery cathode materials.

CN118877958BActive Publication Date: 2025-01-10YIBIN GUANGYUAN LITHIUM BATTERY MATERIALS CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411355604.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2025-01-10
Estimated Expiration
2044-09-27

AI Technical Summary

Technical Problem

In the prior art, the structure of layered transition metal oxide sodium-ion battery cathode materials is prone to change during the insertion and extraction process, leading to battery cycle degradation. Furthermore, the co-precipitation method is prone to forming copper ammonia complexes during copper doping, resulting in failure and making it difficult to control the morphology and particle size distribution.

Method used

A method for preparing a nickel-iron-manganese-copper quaternary cathode material precursor is adopted. Copper elements are gradually filled into the nickel-iron-manganese hydroxide crystal nuclei through a co-precipitation reaction to form a concentration gradient distribution. By using specific complexing agents and precipitants, the particle morphology and density are controlled. Subsequently, it is sintered with a sodium source to form a stable cathode material.

Benefits of technology

It improves the structural stability and capacity of sodium-ion battery cathode materials, simplifies the preparation process, solves the problems of co-precipitation segregation of multiple metal elements and structural instability, and enhances the electrochemical performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118877958B_ABST
    Figure CN118877958B_ABST
Patent Text Reader

Abstract

The invention discloses a nickel-iron-manganese-copper quaternary positive electrode material and its precursor, preparation method and application, belonging to the technical field of battery materials. The chemical formula of the precursor material is Ni a Fe b Mn c Cu d (OH) 2 , where a+b+c+d=1,0<a<1,0
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of battery materials, and in particular to a nickel-iron-manganese-copper quaternary positive electrode material and a precursor, a preparation method and an application thereof. Background Art

[0002] One of the types of sodium cathode materials is transition metal layered oxides (Na x MO2, 0<x≤1, M is a transition metal element), the variable valence transition metals involved are mainly vanadium (V), chromium (Cr), manganese (Mn), iron (Fe), cobalt (Co), nickel (Ni) and copper (Cu), among which manganese and iron, which are relatively abundant in resources, are the most commonly used. Although layered transition metal oxide sodium ion batteries have a high specific capacity, layered transition metals are prone to structural changes or phase transitions during the insertion and extraction of sodium ions, resulting in battery cycle attenuation. Therefore, improving the stability of the positive electrode material is of great significance.

[0003] At present, the modification of layered transition metal oxide positive electrodes is mainly through the introduction of active or inert elements doping or substitution, which can reduce the degree of change in the structure of layered transition metal positive electrode materials during battery operation and improve the conductivity of the materials. Commonly used doping elements are mostly +1 to +4 valence elements, such as copper, nickel, aluminum and titanium.

[0004] In the prior art, there are studies on doping copper in the manganese-iron-nickel system of sodium ion layered positive electrode oxide materials by solid phase synthesis to synthesize a series of compounds with different copper-nickel ratios. However, the synthetic raw materials used in the solid phase method are oxides of various metals, which have problems such as difficult to control morphology, uneven particle size distribution, and high preparation cost. Although the coprecipitation method has a more complicated synthesis method, it has the advantages of uniform product, easy to control morphology, low cost, and low energy consumption. However, for Cu 2+ For example, in the presence of ammonia, Cu easily forms a copper-ammine complex, resulting in the failure of coprecipitation.

[0005] In view of this, the present invention is proposed. Summary of the invention

[0006] The object of the present invention is to provide a nickel-iron-manganese-copper quaternary positive electrode material and its precursor, preparation method and application, so as to solve or improve the above-mentioned technical problems.

[0007] The present invention can be implemented like this:

[0008] In a first aspect, the present invention provides a nickel-iron-manganese-copper quaternary positive electrode material precursor, wherein the chemical formula of the nickel-iron-manganese-copper quaternary positive electrode material precursor is Ni a Fe b Mn c Cu d(OH)2, where a+b+c+d=1, 0<a<1, 0 <b<1,0<c<1,0<d<1;

[0009] The nickel-iron-manganese-copper quaternary positive electrode material precursor is in a granular form, and copper is distributed in a gradient form with gradually increasing concentration from the inside to the outer surface of the nickel-iron-manganese-copper quaternary positive electrode material precursor.

[0010] In an optional embodiment, the nickel-iron-manganese-copper quaternary positive electrode material precursor has at least one of the following characteristics:

[0011] Feature 1: The tap density of the nickel-iron-manganese-copper quaternary cathode material precursor is not less than 1.4g / cm 3 ;

[0012] Feature 2: The specific surface area of ​​the nickel-iron-manganese-copper quaternary positive electrode material precursor is not less than 20m 2 / g;

[0013] Feature 3: D of nickel-iron-manganese-copper quaternary cathode material precursor 50 3μm~10μm.

[0014] In an optional embodiment, the tap density of the nickel-iron-manganese-copper quaternary positive electrode material is not less than 1.45 g / cm 3 , preferably 1.45 g / cm 3 ~1.68g / cm 3 .

[0015] In an optional embodiment, the specific surface area of ​​the nickel-iron-manganese-copper quaternary positive electrode material is not less than 23 m 2 / g, preferably 23m 2 / g~32m 2 / g.

[0016] In an optional embodiment, the D of the nickel-iron-manganese-copper quaternary positive electrode material 50 5μm~6μm.

[0017] In a second aspect, the present invention provides a method for preparing a nickel-iron-manganese-copper quaternary positive electrode material precursor as described in the aforementioned embodiment, comprising the following steps: subjecting a mixed metal salt solution, a first precipitant solution, and a first complexing agent solution to a coprecipitation reaction in a reaction device having a base liquid to obtain a feed liquid having a nickel-iron-manganese hydroxide crystal nucleus; adding a single copper salt solution, a second precipitant solution, and a second complexing agent solution to the feed liquid to continue the reaction so as to fill the pores in the nickel-iron-manganese hydroxide crystal nucleus to generate a nickel-iron-manganese-copper quaternary positive electrode material precursor having a concentration gradient distribution of copper elements;

[0018] Wherein, the mixed metal salt solution is a mixed solution of a soluble nickel salt, a soluble iron salt and a soluble manganese salt;

[0019] The first precipitant solution and the second precipitant solution are independently NaOH solution or KOH solution;

[0020] The first complexing agent in the first complexing agent solution is at least one of ammonia water and a soluble ammonium salt, and the second complexing agent in the second complexing agent solution includes at least one of sodium fluoride, sodium citrate and hydroxyethylethylenediaminetriacetic acid.

[0021] In an optional embodiment, the total concentration of metal ions in the mixed metal salt solution is 1 mol / L to 3 mol / L; an acid is added to the mixed metal salt solution to make the pH value of the mixed metal salt solution 1.0 to 1.5;

[0022] and / or, the concentration of copper ions in the single copper salt solution is 1 mol / L to 3 mol / L;

[0023] And / or, the salt forms of the soluble nickel salt, the soluble iron salt, the soluble manganese salt and the copper salt are independently sulfate, nitrate or halogen salt.

[0024] In an alternative embodiment, the soluble iron salt is a soluble ferrous salt.

[0025] In an alternative embodiment, the acid comprises at least one of dilute sulfuric acid, dilute hydrochloric acid, and dilute nitric acid.

[0026] In an optional embodiment, the mixed metal salt solution is added at a rate of 25 mL / min to 50 mL / min;

[0027] and / or, the addition rate of a single copper salt solution is 25 mL / min to 50 mL / min;

[0028] and / or, the addition rate of the precipitant is 5 mL / min to 20 mL / min, the precipitant is used to control the pH value of the reaction system to be 10 to 12; the concentration of the precipitant in the precipitant solution is 6 mol / L to 12 mol / L;

[0029] And / or, the concentration of the first complexing agent in the reaction system is 2g / L~12g / L, and the concentration of the second complexing agent in the reaction system is 2g / L~12g / L; the mass concentration of the first complexing agent in the first complexing agent solution is 15%~25%, and the mass concentration of the second complexing agent in the second complexing agent solution is 40%~60%.

[0030] In an optional embodiment, the temperature of the coprecipitation reaction is 40°C to 70°C;

[0031] and / or, the stirring speed of the coprecipitation reaction is not less than 300 rpm;

[0032] And / or, the coprecipitation reaction is carried out under a protective atmosphere.

[0033] In an optional embodiment, the stirring speed of the coprecipitation reaction is 300 rpm to 1000 rpm.

[0034] In an optional embodiment, D having a nickel iron manganese hydroxide crystal core 50 0μm~0.1μm smaller than the target particle size, the target particle size is 3μm~10μm.

[0035] In a third aspect, the present invention provides a nickel-iron-manganese-copper quaternary positive electrode material, the precursor of which is the nickel-iron-manganese-copper quaternary positive electrode material precursor of the aforementioned embodiment.

[0036] In a fourth aspect, the present invention provides a method for preparing a nickel-iron-manganese-copper quaternary positive electrode material as described in the aforementioned embodiment, comprising the following steps: pre-sintering a nickel-iron-manganese-copper quaternary positive electrode material precursor after mixing with a sodium source, and sintering after cooling;

[0037] Among them, the pre-sintering temperature is 550℃~650℃, and the pre-sintering time is 8h~12h;

[0038] The sintering temperature is 900°C~1100°C, and the sintering time is 14h~18h.

[0039] In a fifth aspect, the present invention provides a battery comprising the nickel-iron-manganese-copper quaternary positive electrode material of the aforementioned embodiment.

[0040] The beneficial effects of the present invention include:

[0041] The present invention provides a precursor material in which copper is distributed in a gradient form with gradually increasing concentration from the inside to the outside of the precursor material, which is beneficial to improving the structural stability and sintered capacity of the positive electrode precursor of a sodium ion battery. The preparation method is simple and easy to operate, and solves the problems of easy segregation and structural instability of multi-metal element co-precipitation, and can be industrially produced. The positive electrode material prepared from the precursor can improve the electrochemical performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0043] Figure 1 This is a SEM image of the nickel-iron-manganese-copper quaternary positive electrode material precursor prepared in Example 1;

[0044] Figure 2 This is a SEM image of the nickel-iron-manganese-copper quaternary positive electrode material precursor prepared in Comparative Example 1;

[0045] Figure 3 This is a SEM image of the nickel-iron-manganese-copper quaternary positive electrode material precursor prepared in Comparative Example 2;

[0046] Figure 4 This is the SEM image of the nickel-iron-manganese-copper quaternary positive electrode material precursor prepared in Comparative Example 3. DETAILED DESCRIPTION

[0047] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0048] The nickel-iron-manganese-copper quaternary positive electrode material provided by the present invention and its precursor, preparation method and application are described in detail below.

[0049] The present invention provides a nickel-iron-manganese-copper quaternary positive electrode material precursor, the chemical formula of the nickel-iron-manganese-copper quaternary positive electrode material precursor is Ni a Fe b Mn c Cu d (OH)2, where a+b+c+d=1, 0<a<1, 0 <b<1,0<c<1,0<d<1;

[0050] The nickel-iron-manganese-copper quaternary positive electrode material precursor is in a granular form, and copper is distributed in a gradient form with gradually increasing concentration from the inside to the outer surface of the nickel-iron-manganese-copper quaternary positive electrode material precursor.

[0051] In the nickel-iron-manganese-copper quaternary positive electrode material precursor, copper is used as a doping element to improve air stability and capacity. The doping amount of the copper element in the nickel-iron-manganese-copper quaternary positive electrode material precursor gradually increases from the inside of the nickel-iron-manganese-copper quaternary positive electrode material precursor particles to their outer surface.

[0052] In some optional embodiments, the ratio of a:b:c:d can be (2~3):(3~3.5):(3~3.5):(1~3), such as 3:3:3:1 or 2:3.5:3.5:1, etc.

[0053] In some optional embodiments, the tap density of the nickel-iron-manganese-copper quaternary positive electrode material precursor is not less than 1.4 g / cm 3 , such as 1.4g / cm 3 ~1.8g / cm3 , preferably not less than 1.45g / cm 3 , such as 1.45g / cm 3 ~1.68g / cm 3 , for example 1.45g / cm 3 , 1.52g / cm 3 or 1.68 g / cm 3 etc., and can also be 1.45g / cm 3 ~1.68g / cm 3 Other values ​​within the range.

[0054] In some optional embodiments, the specific surface area of ​​the nickel-iron-manganese-copper quaternary positive electrode material precursor is not less than 20 m 2 / g, such as 20m 2 / g~40m 2 / g, preferably not less than 23m 2 / g, such as 23m 2 / g~32m 2 / g, for example 23m 2 / g or 32m 2 / g, etc., can also be 23m 2 / g~32m 2 / Other values ​​within the range of g.

[0055] In some optional embodiments, the D of the nickel-iron-manganese-copper quaternary positive electrode material precursor 50 The diameter is 3 μm to 10 μm, preferably 5 μm to 6 μm, such as 5 μm or 6 μm, or other values ​​within the range of 5 μm to 6 μm.

[0056] As mentioned above, the nickel-iron-manganese-copper quaternary positive electrode material precursor provided by the present invention has the characteristics of high tap density and high specific surface area, and also has high structural stability and capacity.

[0057] Correspondingly, the present invention also provides a method for preparing the above-mentioned nickel-iron-manganese-copper quaternary positive electrode material precursor, comprising the following steps: subjecting a mixed metal salt solution, a first precipitant solution, and a first complexing agent solution to a co-precipitation reaction in a reaction device having a base liquid to obtain a slurry having nickel-iron-manganese hydroxide crystal nuclei; adding a single copper salt solution, a second precipitant solution, and a second complexing agent solution to the slurry for continued reaction to fill the pores in the nickel-iron-manganese hydroxide crystal nuclei to generate a nickel-iron-manganese-copper quaternary positive electrode material precursor in which the copper element is distributed in a concentration gradient.

[0058] The mixed metal salt solution is a mixed solution of a soluble nickel salt, a soluble iron salt and a soluble manganese salt.

[0059] The salt forms of the above-mentioned soluble nickel salt, soluble iron salt, soluble manganese salt and copper salt are independently sulfate, nitrate or halogen salt, preferably sulfate. Among them, the soluble iron salt is a soluble divalent iron salt.

[0060] That is, the soluble nickel salt is nickel sulfate, the soluble iron salt is ferrous sulfate, the soluble manganese salt is manganese sulfate, and the copper salt is copper sulfate.

[0061] In an alternative embodiment, the soluble iron salt is a soluble ferrous salt.

[0062] Acid is added to the mixed metal salt solution to make the pH value of the mixed metal salt solution be 1.0-1.5 (such as 1.0, 1.1, 1.2, 1.3, 1.4 or 1.5, etc.), wherein the acid may illustratively but not limitatively include at least one of dilute sulfuric acid, dilute hydrochloric acid and dilute nitric acid.

[0063] The addition of acid to the mixed metal salt solution can prevent the Fe 2+ Oxidized to Fe 3+ The reason is that Fe 3+ / Fe 2+ Under acidic conditions, the electrode potential is relatively large, and divalent iron ions are not easily oxidized into trivalent iron ions in acidic solutions. At the same time, adding acid can help dissolve insoluble or difficult-to-dissolve tiny particles in the raw materials, avoiding continuous nucleation of particles that causes uneven materials, thereby achieving co-precipitation of various metal ions.

[0064] The first precipitant solution and the second precipitant solution are independently NaOH solution or KOH solution.

[0065] The first complexing agent in the first complexing agent solution is at least one of ammonia water and a soluble ammonium salt (such as ammonium sulfate, etc.), and the second complexing agent in the second complexing agent solution includes at least one of sodium fluoride, sodium citrate and hydroxyethylethylenediaminetriacetic acid.

[0066] It should be noted that the reason why the present invention adopts two complexing agents, specifically setting the first complexing agent to at least one of ammonia water and a soluble ammonium salt, setting the second complexing agent to at least one of sodium fluoride, sodium citrate and hydroxyethylethylenediaminetriacetic acid, and adding the first complexing agent to the reaction system to prepare the crystal nucleus and then adding the second complexing agent is that: in the presence of the first complexing agent, copper ions are prone to form copper-ammine complexes and cause coprecipitation failure. Therefore, the first complexing agent should not be used as a complexing agent in the process of adding copper.

[0067] If the first complexing agent and the second complexing agent are added to the reaction system at the same time, it is easy to cause the particles to have two different morphologies, and the morphologies are difficult to control; if only the first complexing agent is used, it is easy to cause co-precipitation failure and poor doping effect; or if only the second complexing agent is used, the product tap density will be low, affecting the performance.

[0068] In some optional embodiments, the total concentration of metal ions in the mixed metal salt solution can be 1 mol / L~3 mol / L, such as 1 mol / L, 1.5 mol / L, 2 mol / L, 2.5 mol / L or 3 mol / L, etc., or other values ​​within the range of 1 mol / L~3 mol / L.

[0069] The concentration of copper ions in a single copper salt solution may also be 1 mol / L to 3 mol / L, such as 1 mol / L, 1.5 mol / L, 2 mol / L, 2.5 mol / L or 3 mol / L, or other values ​​within the range of 1 mol / L to 3 mol / L.

[0070] The addition rate of the mixed metal salt solution and the addition rate of the single copper salt solution can independently be 25mL / min~50mL / min, such as 25mL / min, 28mL / min, 30mL / min, 32mL / min, 35mL / min, 40mL / min, 45mL / min or 50mL / min, or other values ​​within the range of 25mL / min~50mL / min.

[0071] The addition rate of the precipitant can be 5mL / min~20mL / min, such as 5mL / min, 10mL / min, 11mL / min, 12mL / min, 13mL / min, 14mL / min, 15mL / min or 20mL / min, etc., or other values ​​within the range of 5mL / min~20mL / min. The precipitant is used to control the pH value of the reaction system to be 10~12 (such as 10, 10.5, 11, 11.5 or 12, etc.). The concentration of the precipitant in the precipitant solution can be 6mol / L~12mol / L, such as 6mol / L, 8mol / L, 8.5mol / L, 9mol / L, 9.5mol / L, 10mol / L or 12mol / L, etc., or other values ​​within the range of 6mol / L~12mol / L.

[0072] By adjusting the addition rates of the first complexing agent solution and the second complexing agent solution, the concentration of the first complexing agent in the reaction system is maintained at 2g / L~12g / L (such as 2g / L, 4g / L, 4.5g / L, 5g / L, 5.5g / L, 6g / L, 8g / L, 10g / L or 12g / L, etc.), and the concentration of the second complexing agent in the reaction system is maintained at 2g / L~12g / L (such as 2g / L, 4g / L, 6g / L, 8g / L, 8.5g / L, 9g / L, 9.5g / L, 10g / L, 10.5g / L, 11g / L, 11.5g / L or 12g / L, etc.). The mass concentration of the first complexing agent in the first complexing agent solution may be 15% to 25% (e.g., 15%, 18%, 20%, 22% or 25%), and the mass concentration of the second complexing agent in the second complexing agent solution may be 40% to 60% (e.g., 40%, 45%, 50%, 55% or 60%).

[0073] In some optional embodiments, the base solution is composed of water, a third precipitant solution and a third complexing agent solution, the third precipitant solution is the same as the first precipitant solution, and the third complexing agent solution is the same as the first complexing agent solution. The pH value of the base solution is controlled at 10-12, and the NH3 concentration is controlled at 2g / L-12g / L.

[0074] In some optional embodiments, the coprecipitation reaction temperature can be 40°C to 70°C, such as 40°C, 45°C, 50°C, 55°C, 60°C, 65°C or 70°C, etc., or other values ​​within the range of 40°C to 70°C.

[0075] The stirring speed of the coprecipitation reaction is not less than 300 rpm, and may be 300 rpm to 1000 rpm, such as 300 ppm, 400 ppm, 500 ppm, 600 ppm, 700 ppm, 800 ppm, 900 ppm or 1000 ppm, or other values ​​within the range of 300 rpm to 1000 rpm.

[0076] The above coprecipitation reaction is carried out under a protective atmosphere, and the protective atmosphere may be, for example, a nitrogen atmosphere or an argon atmosphere.

[0077] In some optional embodiments, D having a nickel iron manganese hydroxide crystal core 50 The target particle size is 0 μm to 0.1 μm smaller than the target particle size, and the target particle size is 3 μm to 10 μm. In some typical embodiments, D having a nickel-iron-manganese hydroxide crystal nucleus 50 It can be 4.9μm~5.9μm.

[0078] In the preparation method provided by the present invention, a mixed metal salt solution, a first complexing agent, and a first precipitant are first subjected to a coprecipitation reaction to obtain a nickel-iron-manganese hydroxide crystal nucleus; a single copper salt solution, a second complexing agent, and a second precipitant are then added to continue the reaction to fill the pores of the crystal nucleus and generate a copper-containing multi-sodium electric precursor with a concentration gradient structure. This method successfully solves the problem of easy segregation and structural instability of multi-metal element coprecipitation, and obtains a copper-containing multi-sodium electric precursor with a concentration gradient structure.

[0079] In addition, the present invention also provides a nickel-iron-manganese-copper quaternary positive electrode material, and the precursor of the nickel-iron-manganese-copper quaternary positive electrode material is the above-mentioned nickel-iron-manganese-copper quaternary positive electrode material precursor.

[0080] Correspondingly, the present invention also provides a method for preparing the above-mentioned nickel-iron-manganese-copper quaternary positive electrode material, comprising the following steps: mixing the nickel-iron-manganese-copper quaternary positive electrode material precursor with a sodium source, pre-sintering the mixture, and sintering the mixture after cooling.

[0081] The sodium source may be, by way of example but not limitation, sodium carbonate.

[0082] The usage ratio of the nickel-iron-manganese-copper quaternary positive electrode material precursor to the sodium source can be any value in the range of 1:0.5 to 1:1.0, such as 1:0.5, 1:0.6, 1:0.7, 1:0.8, 1:0.9 or 1:1, etc.

[0083] The pre-sintering temperature may be 550°C to 650°C, such as 550°C, 580°C, 600°C, 620°C or 650°C, etc., or other values ​​within the range of 550°C to 650°C.

[0084] The pre-sintering time may be 8 h to 12 h, such as 8 h, 9 h, 10 h, 11 h or 12 h, etc., or may be other values ​​within the range of 8 h to 12 h.

[0085] The sintering temperature may be 900°C to 1100°C, such as 900°C, 950°C, 1000°C, 1050°C or 1100°C, or other values ​​within the range of 900°C to 1100°C.

[0086] The sintering time may be 14 h to 18 h, such as 14 h, 15 h, 16 h, 17 h or 18 h, or may be other values ​​within the range of 14 h to 18 h.

[0087] Furthermore, the present invention also provides a battery, which contains the above-mentioned nickel-iron-manganese-copper quaternary positive electrode material.

[0088] The battery can have a higher first discharge capacity and a higher capacity cycle retention rate.

[0089] In some embodiments, the first discharge capacity of the battery at 0.1C is not less than 140 mAh / g.

[0090] In some embodiments, the capacity retention rate of the above-mentioned battery after 50 cycles under 1C conditions is not less than 93%.

[0091] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.

[0092] Embodiment 1:

[0093] This embodiment provides a nickel-iron-manganese-copper quaternary positive electrode material precursor, and the preparation method thereof is as follows:

[0094] (1) Prepare the ingredients.

[0095] Nickel sulfate, ferrous sulfate, manganese sulfate and copper sulfate are prepared in a molar ratio of Ni, Fe, Mn and Cu of 3:3:3:1, and pure water is added for stirring and dissolution to prepare a mixed solution of nickel-iron-manganese salt (i.e., a mixed salt solution) with a concentration of 2 mol / L and a single solution of copper sulfate with a concentration of 2 mol / L, and dilute sulfuric acid is added to the mixed solution to adjust the pH value of the mixed solution to 1.2.

[0096] A first precipitant solution in which the precipitant is NaOH is prepared, and the concentration of NaOH in the first precipitant solution is 8 mol / L. The second precipitant is the same as the first precipitant.

[0097] A first complexing agent solution and a second complexing agent solution are prepared, wherein the first complexing agent in the first complexing agent solution is ammonia water, and the mass concentration of the ammonia water is 20%; the second complexing agent in the second complexing agent solution is sodium citrate, and the mass concentration of sodium citrate in the second complexing agent solution is 50%.

[0098] (2) Prepare the bottom liquid of the reactor: add pure water to the reactor until the upper stirring paddle is submerged, heat the system to 50°C and maintain, then add sodium hydroxide solution (same as the first precipitant) to adjust the pH value to 11, and add ammonia solution (same as the first complexing agent) to adjust the NH3 concentration to 5g / L;

[0099] (3) The mixed salt solution was added to the reactor at a flow rate of 30 ml / min, and the first precipitant and the first complexing agent were added at the same time. The first precipitant was added at a rate of 10 mL / min and the pH value of the reaction system (the reaction system here is formed by the base liquid, the first precipitant, the first complexing agent and the mixed salt solution) was maintained at 11. The flow rate of the first complexing agent was maintained at a concentration of 5 g / L in the reaction system. The coprecipitation reaction was carried out at a stirring speed of 500 rpm and under nitrogen gas protection. The pH of the reactor was maintained at 11 until the particles D in the reactor were 50The value grows to 4.9μm to generate nickel-iron-manganese hydroxide crystal nuclei; continue to introduce a single solution of copper sulfate at a flow rate of 30ml / min, and at the same time add a second precipitant (the addition rate of the second precipitant is the same as the addition rate of the first precipitant) and a second complexing agent, maintain the concentration of the second complexing agent in the reaction system at 10g / L, and keep the other conditions unchanged until the doping amount reaches the target ratio, thereby generating nickel-iron-manganese-copper hydroxide with a concentration gradient structure.

[0100] (4) The obtained material is aged, washed, dried, and sieved to obtain a nickel-iron-manganese-copper quaternary positive electrode material precursor.

[0101] The SEM image of the nickel-iron-manganese-copper quaternary positive electrode material precursor prepared in this example is as follows: Figure 1 As shown, the D of the nickel-iron-manganese-copper quaternary positive electrode material precursor 50 5.0μm, tap density 1.45g / cm 3 , with a specific surface area of ​​32m 2 / g.

[0102] Embodiment 2:

[0103] The preparation conditions of this embodiment differ from those of embodiment 1 only in that the reaction temperature is 55°C, the reaction pH is 10.8, and the particles D in the reactor are 50 The value grew to 5.9 μm to obtain nickel-iron-manganese hydroxide crystal nuclei.

[0104] The D of the nickel-iron-manganese-copper quaternary positive electrode material precursor prepared in this example 50 6.0μm, tap density 1.68g / cm 3 , with a specific surface area of ​​23m 2 / g.

[0105] Embodiment 3:

[0106] The preparation conditions of this embodiment differ from those of embodiment 1 only in that the molar ratio of nickel sulfate, ferrous sulfate, manganese sulfate and copper sulfate is 2:3.5:3.5:1 among Ni, Fe, Mn and Cu.

[0107] The D of the nickel-iron-manganese-copper quaternary positive electrode material precursor prepared in this example 50 5.0μm, tap density 1.52g / cm 3 , with a specific surface area of ​​32m 2 / g.

[0108] Embodiment 4:

[0109] This embodiment provides a nickel-iron-manganese-copper quaternary positive electrode material precursor, and the preparation method thereof is as follows:

[0110] (1) Prepare the ingredients.

[0111] Nickel chloride, ferrous chloride, manganese chloride and cupric chloride are prepared in a molar ratio of Ni, Fe, Mn and Cu of 3:3:3:1, and pure water is added for stirring and dissolution to prepare a mixed solution of nickel-iron-manganese salt (i.e., a mixed salt solution) with a concentration of 1 mol / L and a single solution of cupric chloride with a concentration of 1 mol / L, and dilute hydrochloric acid is added to the mixed solution to adjust the pH value of the mixed solution to 1.0.

[0112] A first precipitant solution in which the precipitant is NaOH is prepared, and the concentration of NaOH in the first precipitant solution is 6 mol / L. The second precipitant is the same as the first precipitant.

[0113] A first complexing agent solution and a second complexing agent solution are prepared, wherein the first complexing agent in the first complexing agent solution is ammonia water, and the mass concentration of the ammonia water is 15%; the second complexing agent in the second complexing agent solution is sodium fluoride, and the mass concentration of sodium fluoride in the second complexing agent solution is 40%.

[0114] (2) Prepare the bottom liquid of the reactor: add pure water to the reactor until the upper stirring paddle is submerged, heat the system to 40°C and maintain, then add sodium hydroxide solution (same as the first precipitant) to adjust the pH value to 10, and add ammonia solution (same as the first complexing agent) to adjust the NH3 concentration to 4g / L;

[0115] (3) The mixed salt solution was added to the reactor at a flow rate of 25 ml / min, and the first precipitant and the first complexing agent were added at the same time. The first precipitant was added at a rate of 5 mL / min and the pH value of the reaction system (the reaction system here is formed by the base liquid, the first precipitant, the first complexing agent and the mixed salt solution) was maintained at 10. The flow rate of the first complexing agent was maintained at a concentration of 2 g / L in the reaction system. The coprecipitation reaction was carried out at a stirring speed of 300 rpm and under nitrogen gas protection. The pH of the reactor was maintained at 10 until the particles D in the reactor were 50 The value grows to 4.9μm to generate nickel-iron-manganese hydroxide crystal nuclei; continue to introduce a single solution of cupric chloride at a flow rate of 25ml / min, and at the same time add a second precipitant (the addition rate of the second precipitant is the same as the addition rate of the first precipitant) and a second complexing agent, maintain the concentration of the second complexing agent in the reaction system at 2g / L, and keep the other conditions unchanged until the doping amount reaches the target ratio, thereby generating nickel-iron-manganese-copper hydroxide with a concentration gradient structure.

[0116] (4) Same as Example 1.

[0117] Embodiment 5:

[0118] This embodiment provides a nickel-iron-manganese-copper quaternary positive electrode material precursor, and the preparation method thereof is as follows:

[0119] (1) Prepare the ingredients.

[0120] Nickel nitrate, ferrous nitrate, manganese nitrate and cupric nitrate are prepared in a molar ratio of Ni, Fe, Mn and Cu of 3:3:3:1, and pure water is added for stirring and dissolution to prepare a mixed solution of nickel-iron-manganese salt (i.e., a mixed salt solution) with a concentration of 3 mol / L and a single solution of copper nitrate with a concentration of 3 mol / L, and dilute nitric acid is added to the mixed solution to adjust the pH value of the mixed solution to 1.5.

[0121] A first precipitant solution in which the precipitant is KOH is prepared, and the concentration of KOH in the first precipitant solution is 10 mol / L. The second precipitant is the same as the first precipitant.

[0122] A first complexing agent solution and a second complexing agent solution are prepared, wherein the first complexing agent in the first complexing agent solution is ammonia water, and the mass concentration of the ammonia water is 25%; the second complexing agent in the second complexing agent solution is hydroxyethylethylenediaminetriacetic acid, and the mass concentration of hydroxyethylethylenediaminetriacetic acid in the second complexing agent solution is 60%.

[0123] (2) Prepare the bottom liquid of the reactor: add pure water to the reactor until the upper stirring paddle is submerged, heat the system to 70°C and maintain, then add potassium hydroxide solution (same as the first precipitant) to adjust the pH value to 12, and add ammonia water (same as the first complexing agent) to adjust the NH3 concentration to 6g / L;

[0124] (3) The mixed salt solution was added to the reactor at a flow rate of 50 ml / min, and the first precipitant and the first complexing agent were added at the same time. The first precipitant was added at a rate of 20 mL / min and the pH value of the reaction system (the reaction system here is formed by the base liquid, the first precipitant, the first complexing agent and the mixed salt solution) was maintained at 12. The flow rate of the first complexing agent was maintained at a concentration of 12 g / L in the reaction system. The coprecipitation reaction was carried out at a stirring speed of 1000 rpm and under nitrogen gas protection. The pH of the reactor was maintained at 12 until the particles D in the reactor were 50 The value grows to 4.9μm to generate nickel-iron-manganese hydroxide crystal nuclei; continue to introduce a single solution of copper nitrate at a flow rate of 35ml / min, and at the same time add a second precipitant (the addition rate of the second precipitant is the same as the addition rate of the first precipitant) and a second complexing agent, maintain the concentration of the second complexing agent in the reaction system at 12g / L, and keep the other conditions unchanged until the doping amount reaches the target ratio, thereby generating nickel-iron-manganese-copper hydroxide with a concentration gradient structure.

[0125] (4) Same as Example 1.

[0126] Comparative Example 1:

[0127] The difference between this comparative example and Example 1 is that the first complexing agent and the second complexing agent are added at the same time.

[0128] Specifically, in step (3), the mixed salt solution and the single solution of copper sulfate are added to the reactor at a flow rate of 30 ml / min, and the first precipitant, the first complexing agent and the second complexing agent are added at the same time. The first precipitant is added at a rate of 10 mL / min and the pH value of the reaction system (the reaction system here is formed by the base liquid, the first precipitant, the first complexing agent, the second complexing agent and the mixed salt solution) is maintained at 11. The flow rate of the first complexing agent maintains the concentration of the first complexing agent in the reaction system at 5 g / L, and the flow rate of the second complexing agent maintains the concentration of the second complexing agent in the reaction system at 10 g / L. The coprecipitation reaction is carried out at a stirring speed of 500 rpm and under nitrogen gas protection, and the pH of the reactor is maintained at 11 until the particles D in the reactor are 50 The value grows to 5.0μm, generating nickel-iron-manganese-copper hydroxide.

[0129] The SEM image of the nickel-iron-manganese-copper quaternary positive electrode material precursor prepared in this comparative example is as follows: Figure 2 As shown in the figure, it can be seen that the nickel-iron-manganese-copper quaternary positive electrode material precursor has two different morphologies and uneven precipitation. 50 5.0μm, tap density 0.98g / cm 3 , with a specific surface area of ​​62m 2 / g.

[0130] Comparative Example 2:

[0131] The difference between this comparative example and Example 1 is that the second complexing agent is the same as the first complexing agent, both of which are ammonia water with a mass concentration of 20%. Therefore, it can be regarded as that only the first complexing agent is used.

[0132] Specifically, in step (3), the mixed salt solution is added to the reactor at a flow rate of 30 ml / min, and the first precipitant and the first complexing agent are added at the same time. The first precipitant is added at a rate of 10 mL / min and the pH value of the reaction system (the reaction system here is formed by the base liquid, the first precipitant, the first complexing agent and the mixed salt solution) is maintained at 11. The flow rate of the first complexing agent maintains the concentration of the first complexing agent in the reaction system at 5 g / L. The coprecipitation reaction is carried out at a stirring speed of 500 rpm and under nitrogen gas protection. The pH of the reactor is maintained at 11 until the particles D in the reactor are 50The value grows to 4.9μm to generate nickel-iron-manganese hydroxide crystal nuclei; continue to introduce a single solution of copper sulfate at a flow rate of 30ml / min, and at the same time add the second precipitant (the addition rate of the second precipitant is the same as the addition rate of the first precipitant) and the first complexing agent, maintain the concentration of the first complexing agent in the reaction system at 5g / L, and keep the other conditions unchanged until the doping amount reaches the target ratio, thereby generating nickel-iron-manganese-copper hydroxide with a concentration gradient structure.

[0133] The SEM image of the nickel-iron-manganese-copper quaternary positive electrode material precursor prepared in this comparative example is as follows: Figure 3 As shown, the D of the nickel-iron-manganese-copper quaternary positive electrode material precursor 50 5.0μm, tap density 1.24g / cm 3 , with a specific surface area of ​​27m 2 / g.

[0134] Comparative Example 3:

[0135] The difference between this comparative example and Example 1 is that the first complexing agent and the second complexing agent are the same, both sodium citrate, and the mass concentration of sodium citrate in the complexing agent solution is 50%. Therefore, it can be regarded as that only the second complexing agent is used.

[0136] Specifically, in step (3), the mixed salt solution is added to the reactor at a flow rate of 30 ml / min, and the first precipitant and the second complexing agent are added at the same time. The first precipitant is added at a rate of 10 mL / min and the pH value of the reaction system (the reaction system here is formed by the base liquid, the first precipitant, the second complexing agent and the mixed salt solution) is maintained at 11. The flow rate of the second complexing agent maintains the concentration of the first complexing agent in the reaction system at 10 g / L. The coprecipitation reaction is carried out at a stirring speed of 500 rpm and under nitrogen gas protection. The pH of the reactor is maintained at 11 until the particles D in the reactor are 50 The value grows to 4.9μm to generate nickel-iron-manganese hydroxide crystal nuclei; continue to introduce a single solution of copper sulfate at a flow rate of 30ml / min, and at the same time add the second precipitant (the addition rate of the second precipitant is the same as the addition rate of the first precipitant) and the first complexing agent, maintain the concentration of the second complexing agent in the reaction system at 10g / L, and keep the other conditions unchanged until the doping amount reaches the target ratio, thereby generating nickel-iron-manganese-copper hydroxide with a concentration gradient structure.

[0137] The SEM image of the nickel-iron-manganese-copper quaternary positive electrode material precursor prepared in this comparative example is as follows: Figure 4 As shown in the figure, it can be seen that the particle size distribution of the nickel-iron-manganese-copper quaternary positive electrode material precursor is uneven. 50 5.0μm, tap density 1.18g / cm 3 , with a specific surface area of ​​52m2 / g.

[0138] Test example:

[0139] ①. The structures of the nickel-iron-manganese-copper quaternary positive electrode material precursors prepared in the above Examples 1 to 3 and Comparative Examples 1 to 3 were compared, and the results are shown in Table 1.

[0140] Table 1 Test results

[0141]

[0142] ②. The nickel-iron-manganese-copper quaternary positive electrode material precursors prepared in Examples 1 to 3 and Comparative Examples 1 to 3 were respectively prepared into positive electrode materials according to the following methods: each precursor was mixed with sodium carbonate at a molar ratio of 1:0.65 between the transition metal element in the precursor and the sodium in the sodium carbonate, and then pre-sintered at 600°C for 10 hours. After cooling to room temperature in the furnace, the mixture was sintered again at 1000°C for 16 hours, and naturally cooled to room temperature to obtain the positive electrode material.

[0143] Furthermore, each positive electrode material was mixed with a conductive agent (carbon black) and a binder (PVDF) at a mass ratio of 90:5:5, and then made into a slurry and coated on an aluminum foil to obtain a pole piece. A half-cell with sodium metal as the counter electrode, in which the diaphragm was selected as glass fiber and the electrolyte was an organic solution of sodium perchlorate as the electrolyte, was assembled into a half-cell, and the electrochemical performance of the positive electrode material was tested. The electrochemical performance test results are shown in Table 2.

[0144] The test conditions are: conduct charge and discharge tests in the voltage range of 2V~4.1V, test the 0.1C first discharge capacity and the capacity retention rate of 1C cycle 50 cycles.

[0145] Table 2 Test results

[0146]

[0147] It can be seen from Table 2 that the battery prepared by the nickel-iron-manganese-copper quaternary positive electrode material precursor provided by the embodiment of the present invention has better electrochemical performance than the control example.

[0148] In summary, the nickel-iron-manganese-copper quaternary positive electrode material precursor proposed in the present invention has a concentration gradient structure, the copper doping amount of the particles gradually increases from the inside to the outer surface, and has the characteristics of high tap density and high specific surface area; the problem of difficulty in co-precipitation of nickel-iron-manganese-copper is solved by stepwise addition of different salt solutions and chelating agents, and the positive electrode material sintered using the precursor has excellent electrochemical performance.

[0149] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a nickel-iron-manganese-copper quaternary positive electrode material precursor, characterized in that: The following steps are involved: A mixed metal salt solution, a first precipitant solution, and a first complexing agent solution are subjected to a coprecipitation reaction in a reaction device having a base liquid to obtain a feed liquid having a nickel-iron-manganese hydroxide crystal nucleus; a single copper salt solution, a second precipitant solution, and a second complexing agent solution are added to the feed liquid to continue the reaction so as to fill the pores in the nickel-iron-manganese hydroxide crystal nucleus to generate a nickel-iron-manganese-copper quaternary positive electrode material precursor having a concentration gradient distribution of copper elements; Wherein, the mixed metal salt solution is a mixed solution of a soluble nickel salt, a soluble iron salt and a soluble manganese salt; The first precipitant solution and the second precipitant solution are independently NaOH solution or KOH solution; The first complexing agent in the first complexing agent solution is at least one of ammonia water and a soluble ammonium salt, and the second complexing agent in the second complexing agent solution includes at least one of sodium fluoride, sodium citrate and hydroxyethylethylenediaminetriacetic acid; The chemical formula of the nickel-iron-manganese-copper quaternary positive electrode material precursor is Ni a Fe b Mn c Cu d (OH)2, where a+b+c+d=1, 0<a<1, 0 <b<1,0<c<1,0<d<1; The nickel-iron-manganese-copper quaternary positive electrode material precursor is in a granular form, and copper is distributed in a gradient form with gradually increasing concentration from the inside to the outer surface of the nickel-iron-manganese-copper quaternary positive electrode material precursor; The tap density of the nickel-iron-manganese-copper quaternary positive electrode material precursor is not less than 1.4 g / cm 3 ; The specific surface area of ​​the nickel-iron-manganese-copper quaternary positive electrode material precursor is not less than 20 m 2 / g; The nickel-iron-manganese-copper quaternary positive electrode material precursor D 50 3μm~10μm.

2. The preparation method according to claim 1, characterized in that: In the mixed metal salt solution, the total concentration of metal ions is 1 mol / L to 3 mol / L; an acid is added to the mixed metal salt solution so that the pH value of the mixed metal salt solution is 1.0 to 1.5; and / or, the concentration of copper ions in the single copper salt solution is 1 mol / L to 3 mol / L; And / or, the salt forms of the soluble nickel salt, soluble iron salt, soluble manganese salt and copper salt are independently sulfate, nitrate or halogen salt.

3. The preparation method according to claim 1, characterized in that: The addition rate of the mixed metal salt solution is 25 mL / min~50 mL / min; And / or, the single copper salt solution is added at a rate of 25 mL / min to 50 mL / min; And / or, the addition rate of the precipitant is 5 mL / min~20 mL / min, the precipitant is used to control the pH value of the reaction system to 10~12; the concentration of the precipitant in the precipitant solution is 6 mol / L~12 mol / L; And / or, the concentration of the first complexing agent in the reaction system is 2g / L~12g / L, and the concentration of the second complexing agent in the reaction system is 2g / L~12g / L; the mass concentration of the first complexing agent in the first complexing agent solution is 15%~25%, and the mass concentration of the second complexing agent in the second complexing agent solution is 40%~60%.

4. The preparation method according to claim 1, characterized in that: The temperature of the coprecipitation reaction is 40°C~70°C; and / or, the stirring speed of the coprecipitation reaction is not less than 300 rpm; And / or, the coprecipitation reaction is carried out under a protective atmosphere.

5. The preparation method according to claim 1, characterized in that: The D having nickel iron manganese hydroxide crystal nucleus 50 0 μm to 0.1 μm smaller than the target particle size, and the target particle size is 3 μm to 10 μm.

6. A nickel-iron-manganese-copper quaternary positive electrode material, characterized in that: The precursor of the nickel-iron-manganese-copper quaternary positive electrode material is a nickel-iron-manganese-copper quaternary positive electrode material precursor prepared by the preparation method described in any one of claims 1 to 5.

7. A method for preparing the nickel-iron-manganese-copper quaternary positive electrode material as claimed in claim 6, characterized in that: The following steps are involved: The nickel-iron-manganese-copper quaternary positive electrode material precursor is mixed with a sodium source and then pre-sintered, and then sintered after cooling; Among them, the pre-sintering temperature is 550℃~650℃, and the pre-sintering time is 8h~12h; The sintering temperature is 900°C~1100°C, and the sintering time is 14h~18h.

8. A battery, characterized in that: The battery contains the nickel-iron-manganese-copper quaternary positive electrode material as described in claim 6.

Citation Information

Patent Citations

  • Gradient-doped oxide positive electrode material for sodium ion battery and preparation method of gradient-doped oxide positive electrode material

    CN117878324A